2022
DOI: 10.1093/nar/gkac861
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic transactivation domain of EZH2 binds AR and AR’s splice variant, promoting oncogene activation and tumorous transformation

Abstract: Enhancer of Zeste Homolog 2 (EZH2) and androgen receptor (AR) are crucial chromatin/gene regulators involved in the development and/or progression of prostate cancer, including advanced castration-resistant prostate cancer (CRPC). To sustain prostate tumorigenicity, EZH2 establishes non-canonical biochemical interaction with AR for mediating oncogene activation, in addition to its canonical role as a transcriptional repressor and enzymatic subunit of Polycomb Repressive Complex 2 (PRC2). However, the molecular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
(108 reference statements)
2
7
0
Order By: Relevance
“…Treating with an EZH2 inhibitor also drastically reduced the number of called FLAG-β-catenin peaks in both EV and PTEN KD cells. These findings are consistent with other findings in which EZH2 induced the binding of AR, cMyc, and P300 to the chromatin to mediate gene expression (34,35). While previous studies suggest that EZH2 methylation of other non-histone proteins leads exclusively to gene activation or repression (19,20), our findings propose a model in which EZH2-mediated β-catenin methylation increases β-catenin’s binding to the chromatin and fine-tunes β-catenin activity to both repress and activate gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…Treating with an EZH2 inhibitor also drastically reduced the number of called FLAG-β-catenin peaks in both EV and PTEN KD cells. These findings are consistent with other findings in which EZH2 induced the binding of AR, cMyc, and P300 to the chromatin to mediate gene expression (34,35). While previous studies suggest that EZH2 methylation of other non-histone proteins leads exclusively to gene activation or repression (19,20), our findings propose a model in which EZH2-mediated β-catenin methylation increases β-catenin’s binding to the chromatin and fine-tunes β-catenin activity to both repress and activate gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…While one of the principal reasons underpinning the success of this approach is that LSD1 plays a Frontiers in Cell and Developmental Biology frontiersin.org critical role in the regulation of expression of genes involved in the differentiation of hematopoietic stem cells (Kerenyi et al, 2013), it is noteworthy that a non-canonical scaffolding role for LSD1 has also been identified in APL (Ravasio et al, 2020). Recent research has demonstrated that EZH2 also performs canonical as well as potentially opposing non-canonical roles in multiple types of cancer (Wang and Wang, 2020;Anwar et al, 2021;Huang et al, 2021;Wang et al, 2022a;Wang et al, 2022b;Poplineau et al, 2022), and our results indicate that this is also true in the context of myeloid differentiation. Our study suggests both anti-and pro-differentiative roles for EZH2 in AML and that SAM-competitive inhibition by GSK-343 interferes with both, thus impeding differentiation by ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…One of the non-canonical roles that has emerged for EZH2, which may be relevant to this study, is as a transcriptional activator independent of PRC2 and H3K27 methylation. It has recently been reported that EZH2 contains a cryptic transactivation domain (TAD) that mediates direct interactions with p300 (EP300) and MYC ( Jiao et al, 2020 ; Wang et al, 2022b ), as well as another member of the nuclear receptor superfamily, androgen receptor (AR) ( Wang et al, 2022a ). p300 is an important mediator of ATRA-induced, RXR/RARα-mediated transcriptional activation ( Blobel, 2000 ), functioning both as an acetyltransferase and a scaffolding protein via direct interaction with the RXR/RARα heterodimer ( Chan and La Thangue, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…VHL protein, together with elongin B and C, Cullin 2, and RBX‐1, is part of a multiprotein complex with E3 ubiquitin ligase activity. 113 , 114 , 115 , 116 , 117 , 118 In the complex, VHL is responsible for binding to specific substrates, most notably hypoxia‐inducible factor (HIF‐1 α), for its ubiquitination and proteasome degradation. 119 , 120 In 2012, Crews group disclosed the first small‐molecule ligands for VHL E3 ligase based on skeleton of hydroxyproline.…”
Section: Vhl Ligands and Their Utilizations In Protacs For Cancer Dru...mentioning
confidence: 99%